축구와 국제평화: 소통과 정치적 힘, 차별금지, 협력과 희망의 매개체 - 김석수; Suk Soo Kim (글로벌정치연구, 2008)
축구는 단순한 운동경기가 아니라 인간 삶을 규정하는 방식이 되었다. 축구는 종교만큼이나 깊은 뿌리를 갖고 있고, 국가와 사회의 공동체 조직의 일부로 기능해 왔다. 축구는 암울한 시기에 스스로 문화적 자부심과 정체성을 펼칠 수 있는 장이었고, 답답하고 불쾌한 분위기 속에서 축구가 서로를 단합할 수 있도록 도와주는 역할을 해 왔다. 그러나 인터넷과 위성의 발달과 확산으로 축구는 최고의 스포츠가 되었다. 전 세계를 통해서 사람들은 빅리그 경기를 시청할 수 있게 되었다. 이것은 아프리카 사람들이 축구를 통해 미래의 꿈과 희망을 가지는 것이 가능해졌다. 축구의 세계화는 축구경기를 통해서 각 문화와 혈통, 민족과 인종, 지역과 지역 사이의 반목 관계를 약화시킬 수 있는 것을 보여주고 있다. 축구와 축구경기, 축구공은 인류문명의 새로운 아이콘이 되었다. 축구공 속에서 인류의 평화와 인류애 같은 문명의 아름다운 가치와 적성이 내장되어 있다. 축구는 축구자본주의화에 따른 어두운 면에 대한 관심과 배려에 노력하고 있다. 특히 아프리카에서는 민족의 단합과 평화와 협력과 희망의 매개로서 역할을 하고 있다. 신은 인간을 만들었고, 인간은 축구를 만들었고, 인간은 축구를 통해서 야만에서 문명(신사)으로 진화되었다. Football has become not a simple sport but a way that regulates the life of human being. Football has as much a deep root as religion and has functioned a part of social national community. Football was a field that could show its cultural pride and identity in the hard times. Football has played a role in help to unify one another. Owing to the development and spread of Internet and satellite, football has become a primary sports in the world. Through out the world, people can watch the game of Big League. It enables African to dream and hope in the future. Football`s globalization illustrates that every culture and family line, nationality and ethnic, region and religion can reduce its hostile relations through a football game. Football and football game, a soccer ball are a new icon. A beautiful human value and instinct of civilization like human`s peace and humanity are contained in a soccer ball. Particularly, football plays a part in national unifying, peace and cooperation, tool of hope in Africa. God created a Man and the Man made a football, furthermore human has evolved from barbarism to gentleman through the football.